2016
DOI: 10.1002/slct.201600478
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal EndophyteNigrospora oryzaeProduces Quercetin Monoglycosides Previously Known Only from Plants

Abstract: Three quercetin‐3‐O‐glycosides (1–3) were obtained from the endophytic fungus Nigrospora oryzae isolated from leaves of the Nigerian mistletoe Loranthus micranthus. The compounds were unequivocally identified based on their one and two dimensional NMR spectra and on their mass spectra. A fourth flavonoid glycoside (4) was tentatively identified as a luteolin monoglycoside. Comparative HPLC analyses of extracts of the endophyte and of the host plant indicated that compounds (1–3) were present as minor constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…These compounds can be classified as antibiotics, antioxidants, anticancer agents, volatile antimicrobial agents, immunosuppressive compounds, plant growth promoting agents, and insecticides (1). It has been reported that endophytes possess the ability to produce the same or similar chemicals as those originating from their host plants (2,3). This presents endophytic microorganisms as potential alternatives to plants in the search for biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can be classified as antibiotics, antioxidants, anticancer agents, volatile antimicrobial agents, immunosuppressive compounds, plant growth promoting agents, and insecticides (1). It has been reported that endophytes possess the ability to produce the same or similar chemicals as those originating from their host plants (2,3). This presents endophytic microorganisms as potential alternatives to plants in the search for biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Tel: +2348063809147 bioactive molecules. [7][8][9][10][11][12][13][14][15] Only a few studies on the presence of endophytes in citrus plants have been performed and little is known about the microbial endophytic community of the citrus plants. [16][17][18][19] Several endophytic bacterial species have however been isolated from Citrus jambhiri.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, compound 1 was established as kaempferol 3‐ O ‐[ α ‐rhamnopyranosyl‐(1→6)‐3‐ O ‐acetyl‐ β ‐galactopyranoside] and named 3′′‐ O ‐acetyl biorobin. Remarkably, glycosylation reactions by adding galactose vs. glucose to precursors are rare for fungi . Galactose, however, is also found as a structural moiety of the pyrenopolyene C ‐glycoside epipyrone A which is present in all extracts of E. nigrum analyzed in this study (Figures –) indicating the capacity of the fungus to use galactose for glycosylation reactions …”
Section: Resultsmentioning
confidence: 67%